2021
DOI: 10.1371/journal.pone.0244806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on cytokines levels in gingival crevicular fluid and saliva and on clinical periodontal parameters of middle-aged and elderly patients with type 2 diabetes mellitus

Abstract: Objective To analyze the effect of statins on cytokines levels in gingival crevicular fluid (GCF) and saliva and on clinical periodontal parameters of middle-aged and elderly patients with type 2 diabetes mellitus (T2DM). Methods Systemically healthy controls (C group, n = 62), T2DM patients not taking statins (D group, n = 57) and T2DM patients taking statins (S group, n = 24) were recruited. In each group, subjects (40–85 years) were subclassified into the h (periodontal health)group, the g (gingivitis)gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Additionally, during the 30-day culture period, we quantified the baseline inflammatory profile of the MOUTH model by multiplexed fluorescent bead-based immunoassay and observed that the prevalence of the analytes surveyed (Supplementary Fig. 1) was consistent with observed inflammatory cytokine and chemokine profiles of gingival cervicular fluid from periodontally healthy human subjects [31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Similar to other in vitro gingival tissue models using both submerged and ALI culture methods 15 , MOUTH tissue morphology maintained five to eight layers of keratinocytes measuring up to 200 µm thick.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, during the 30-day culture period, we quantified the baseline inflammatory profile of the MOUTH model by multiplexed fluorescent bead-based immunoassay and observed that the prevalence of the analytes surveyed (Supplementary Fig. 1) was consistent with observed inflammatory cytokine and chemokine profiles of gingival cervicular fluid from periodontally healthy human subjects [31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Similar to other in vitro gingival tissue models using both submerged and ALI culture methods 15 , MOUTH tissue morphology maintained five to eight layers of keratinocytes measuring up to 200 µm thick.…”
Section: Discussionmentioning
confidence: 60%
“…Similar studies in individuals with no T2D have been conflicting. Some studies reported associations between statin use and lesser periodontitis severity 26,27,48,50 ; two studies showed little relationship between statin use and tooth loss. 49,51 A retrospective study by Cunha-Cruz et al from 1021 individuals reported that any statin use during the first 3 years after the initial periodontal exam was associated with a 48% reduction in tooth loss in subsequent years.…”
Section: Discussionmentioning
confidence: 99%
“…Inayat et al revealed that inflammation-associated genes were upregulated in peripheral blood leukocytes in T2DM patients, while metformin was demonstrated to be an anti-inflammatory reagent, that appeared to be independent of its anti-hyperglycemic activity in T2DM patients [22]. IL-7 levels are increased in gingival crevicular fluid and saliva and in clinical periodontal parameters of middle-aged and elderly T2DM patients [23]. Elevated IL-15 expression alters the biological behavior of trophoblasts in vitro and contributes to the placental pathology in gestational diabetes mellitus [24].…”
Section: Plasma Cytokine Detectionmentioning
confidence: 99%